(untitled) (International Journal of Food and Nutritional Sciences, 2019)
In this work, a new L-shape CPW quadrant patch antenna is designed and simulated using an electromagnetic solver for wireless band applications. The proposed antenna consists of an Lshape CPW plane (Conventional coplanar waveguide) with a quadrant patch.